How do you combine like terms in 2( x ^ { 2} + 4x + 2) + 4( x ^ { 2} + 3x - 2)2(x2+4x+2)+4(x2+3x2)?

2 Answers
May 22, 2018

6x^2 +20x -46x2+20x4

Explanation:

Expand.

2x^2 +8x +4 +4x^2 +12x -82x2+8x+4+4x2+12x8

Collect the like terms.

2x^2 +4x^2 =6x^22x2+4x2=6x2

8x +12x=20x8x+12x=20x

and 4+(-8) =-44+(8)=4

So 6x^2 +20x -46x2+20x4

May 22, 2018

2(x^2+4x+2)+4(x^2+3x-2)=color(blue)(6x^2+20x-42(x2+4x+2)+4(x2+3x2)=6x2+20x4

Explanation:

Simplify:

2(x^2+4x+2)+4(x^2+3x-2)2(x2+4x+2)+4(x2+3x2)

Expand 2(x^2+4x+2)2(x2+4x+2).

2x^2+8x+4+4(x^2+3x-2)2x2+8x+4+4(x2+3x2)

Expand 4(x^2+3x-2)4(x2+3x2).

2x^2+8x+4+4x^2+12x-82x2+8x+4+4x2+12x8

Collect like terms.

(2x^2+4x^2)+(8x+12x)+(4-8)(2x2+4x2)+(8x+12x)+(48)

Combine like terms.

6x^2+20x-46x2+20x4